Gamification – tests of strength in the digital space from an educator's perspective - Jaskóné Gácsi Mária (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. Public education faces challenges in today's technology-rich world and how to effectively channel technology into education is an important question. The importance of the learning environment is not a matter of debate, but there are a number of implications that need to be mentioned. For example, the growing trend towards gamification and tests that allow instant assessment, which point to a revival of behaviourism's theory of learning and how it shapes our understanding of learning. Of course, theories of learning are constantly co-existing in pedagogical thinking, for example social constructivism is making a comeback in online collaborative learning.
Keywords: gamification; digital space; education